Windows on worlds : international collections at Indiana University - O'Meara, Patrick; Peck, Leah K. (Well house, 2020)
"Indiana University Bloomington houses exceptional materials from nearly every continent. Windows on Worlds: International Collections at Indiana University takes readers on a visual journey through IU's collections like never before. Ranging in works as diverse as painting, sculpture, costume, rare manuscripts, musical instruments, and much more-the museums, institutes, collections, and other holdings on IU's flagship campus provide unique engagement opportunities for students, researchers, and members of the public. Windows on Worlds showcases the unique and unexpected items from collections across the Bloomington campus, such as the Boulle clock in the Federal Room of the Indiana Memorial Union; the Burmese headdresses in the Mathers Museum of World Culture (now the IU Museum of Archaeology and Anthropology); the fish-shaped coffin in the Sidney and Lois Eskenazi Museum of Art; the rare manuscripts and puzzles of the world-famous Lilly Library; and, finally, new additions on campus like the IU Metz Carillon. Brimming with beautiful photographs, this book offers readers insight into an extraordinary number of cultures and societies through IU's collections"--